Performance of a points-based scoring system for assessing species limits in birds. Issue 2 (9th April 2021) - Tobias, Joseph A; Donald, Paul F; Martin, Rob W; Butchart, Stuart H M; Collar, Nigel J
Abstract: Species are fundamental to biology, conservation, and environmental legislation; yet, there is often disagreement on how and where species limits should be drawn. Even sophisticated molecular methods have limitations, particularly in the context of geographically isolated lineages or inadequate sampling of loci. With extinction rates rising, methods are needed to assess species limits rapidly but robustly. Tobias et al. devised a points-based system to compare phenotypic divergence between taxa against the level of divergence in sympatric species, establishing a threshold to guide taxonomic assessments at a global scale. The method has received a mixed reception. To evaluate its performance, we identified 397 novel taxonomic splits from 328 parent taxa made by application of the criteria (in 2014‒2016) and searched for subsequent publications investigating the same taxa with molecular and/or phenotypic data. Only 71 (18%) novel splits from 60 parent taxa have since been investigated by independent studies, suggesting that publication of splits underpinned by the criteria in 2014–2016 accelerated taxonomic decisions by at least 33 years. In the evaluated cases, independent analyses explicitly or implicitly supported species status in 62 (87.3%) of 71 splits, with the level of support increasing to 97.2% when excluding subsequent studies limited only to molecular data, and reaching 100% when the points-based criteria were applied using recommended sample sizes. Despite the fact that the training set used to calibrate the criteria was heavily weighted toward passerines, splits of passerines and non-passerines received equally strong support from independent research. We conclude that the method provides a useful tool for quantifying phenotypic divergence and fast-tracking robust taxonomic decisions at a global scale. Lay Summary: A scoring system based on quantitative criteria was developed for classifying bird species and applied to the global avifauna in 2014–2016. We assess the performance of the criteria by searching for independent taxonomic assessments published subsequently. A minimum of 87% of novel taxonomic splits proposed by the criteria are supported by independent research, increasing to 97–100% when focusing only on integrative analyses based on genotypic and phenotypic information, or when the criteria were applied using more robust samples of individuals. The proportion of novel splits assessed by subsequent independent studies suggests that the application of the criteria in 2014–2016 accelerated taxonomic decisions by at least 33 years. We conclude that the criteria offer a useful tool for fast-tracking robust taxonomic decisions, although they do not remove the need for verification by more sophisticated analyses.